Peer and parental sources of influence regarding interracial and same‐race peer encounters. (8th December 2021) - Burkholder, Amanda R.; Glidden, Jacquelyn; Yee, Kathryn M.; Cooley, Shelby; Killen, Melanie
Abstract: This study investigated the socializing influence of peers and parents in interracial encounters by disentangling how children and adolescents consider peer and parent messages when predicting interracial and same‐race inclusion. Black and White children (9–14 years old, N = 246) predicted the likelihood of interracial and same‐race peer inclusion when peer and parent sources of influence were present and provided justifications for their expectations. Results revealed that, while participants predicted inclusion would be less likely when parent sources of influence were present than when peer sources of influence were present, the racial composition of the encounter and the race of the participant mattered only in contexts with peer sources of influence. Participants' reasoning about the benefits of inclusion and social pressure also differed when parent or peer sources were present. This study informs efforts to improve the quality of interracial peer interactions and programs designed to promote positive intergroup peer relationships.